DSC Modelling for Predicting Resilient Modulus of Crushed Rock Base as a Road Base Material for Western Australia Roads - Khobklang, Pakdee; Vimonsatit, Vanissorn; Jitsangiam, Peerapong; Nikraz, Hamid (International Society for Asphalt Pavements (ISAP), 2012)
Crush Rock Base (CRB) is a commonly used road base material for Western Australia Roads. In order to increase the efficiency of using this material in pavement structure design, material modelling for analysis which is based on experimental results needs to be investigated. This paper is a preliminary study of the use of the Disturbed State Concept (DSC) to predict the resilient modulus for CRB. DSC was adopted as the modelling approach because of its simplicity and yet is powerful in capturing the elastic and inelastic responses of materials to loading. The main assumption of DSC is that the actual material deformation, at any loading state, can be determined from its assumed relative intact (RI) state. The DSC equation of CRB has been constructed by using a set of the experimental results of the resilient modulus tests and an idealised material model, namely the linear elastic model, of the relative intact (RI) part was considered. The results reveal that the resilient modulus-applied stress relationships, which were back-predicted using the DSC modelling, were consistent with the experimental results. The DSC equation, which is suited for predicting the resilient modulus of CRB specimens, will then be introduced.